3D Bioconvective multiple slip flow of chemically reactive Casson nanofluid with gyrotactic micro‐organisms. Issue 1 (15th October 2019) - Nayak, M. K.; Prakash, J.; Tripathi, D.; Pandey, V. S.; Shaw, S.; Makinde, O. D.
Abstract: In the present study, we investigate the velocity, thermal, solutal, and motile micro‐organism (MM) slip effects on the flow of chemically reactive Casson nanofluid flowing over an exponentially stretched electromagnetic sheet in the presence of a chemical reaction. In addition, a mechanism of improving the motion of nanoparticles (Brownian motion and thermophoresis) is incorporated. The nondimensionalized ordinary differential equations are tackled by using symbolic computation software, MATLAB 2012b, with bvp4c function. Some significant and relevant characteristics of associated profiles are displayed graphically and discussed beautifully with the aid of tables through comprehensive numerical computations. The results of the study show that elevated Casson fluid parameter, gyrotactic micro‐organism, and electromagnetic strength belittle both axial as well as transverse velocities and the related momentum boundary layer thickness. Another important outcome is that low Prandtl fluids and enhancement in the strength of electromagnetic field fasten the diffusion of micro‐organisms, thereby augmenting the density of MM in the related boundary layer.